Photo-electrochemical properties of TiOs2 nanotube arrays: effect of different polishing method of Ti substrate prior to anodization in fluoride-H2O2-containing electrolyte. (February 2019) - Budiman, H; Wibowo, R; Zuas, O; Gunlazuardi, J
Abstract: The comparison of two pre-treatment methods, such as mechanical polishing and chemical polishing, prior to anodization of titanium surface in the ethylene glycol based electrolyte containing H2 O2, were carried out to investigate their effects on photo-electrochemical property of produced highly ordered TiO2 nanotube arrays (HOTNAs). The Ti-chemical polishing was conducted in electrolyte containing H2 O2 (0.6% H2 O2 /1.4% H2 O). The prepared HOTNAs were characterized by FT-IR, UV-Vis DRS and SEM. The obtained FTIR spectrum, showed vibration band at 1100 and 425 cm −1, give strong indication on the existent of a -Ti-O-Ti-network. While from UV-Vis DRS spectra, the band gap of the fabricated HOTNAs were found in the range of 3.10-3.22 eV, which are characteristics for anatase phase. In addition, obtained SEM image indicates the existence of quite good ordered nanotube arrays morphology. Linear sweep voltammetry (LSV) measurement showed that the steady state photocurrent density of HOTNAs fabricated by Ti-chemical polishing were greater than that of prepared by Ti-mechanical polishing. The increasing of H2 O2 content in electrolyte (1.5% H2 O2 /3.5% H2 O) affected to the enhancement of steady state photocurrent density of HOTNAs. Thus pre-treatment of the Ti foils using chemical polish method does enhance its photo-electrochemical property.